Control mechanisms of slope, highland & hilly area in managing landslides occurrence: a comparative legal study between Hong Kong and Malaysia / Nurarnida Sabrina Mohd Sabri … [et al.] - Mohd Sabri, Nurarnida Sabrina; Mohamed Azmi, Nur Hidayah; Abd Wahab, Izzati; Mohd Latiff, Norashikin (Faculty of Law, 2013)
Modernization has caused rapid development in our country. This can be seen where nowadays thousands of buildings are built almost everywhere. Buildings are built on earth surface that covers slope, highland and hilly area. This is where environmental law comes into picture to restrain or stop any development that brings danger to the society and nature. Therefore, it is a reminder that to be a modern country it is not necessary we violate nature. The purpose of this study is to propose comprehensive and efficient laws on enforcement and implementation for managing landslides occurrences' in Malaysia. Apart from that, a comparison has been made between laws in our country with Hong Kong on matter regarding the enforcement and implementation in managing landslides. In conclusion, this research also will examine the existing laws and guidelines (if any) in Malaysia as well as in Hong Kong.